1997
DOI: 10.1111/j.1528-1157.1997.tb05201.x
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy Trials of New Antiepileptic Drugs

Abstract: Antiepileptic drugs (AEDs) administered as monotherapy are the preferred treatment regimen for most patients with epilepsy. Monotherapy offers several advantages over polytherapy, including avoidance of drug interactions, fewer adverse effects, greater ease of administration, and decreased cost. The more recently available AEDs, such as gabapentin (GBP), lamotrigine (LTG), and topiramate (TPM), are presently approved by the Food and Drug Administration (FDA) as add-on therapy for treatment of partial-onset sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 14 publications
(4 reference statements)
0
34
1
Order By: Relevance
“…Monotherapy studies with gabapentin (GBP) have recently been completed (22). GBP was particularly well tolerated in add-on trials and in monotherapy comparisons with CBZ (23).…”
Section: Gabapentinmentioning
confidence: 99%
“…Monotherapy studies with gabapentin (GBP) have recently been completed (22). GBP was particularly well tolerated in add-on trials and in monotherapy comparisons with CBZ (23).…”
Section: Gabapentinmentioning
confidence: 99%
“…3) was first shown to be an effective anticonvulsant agent in different animal models of epilepsy [154]. In humans, it prevents partial and generalized tonicclonic seizures when prescribed as monotherapy or with other drugs [155][156][157]. In animal models, gabapentin appears to block nociceptive responses, producing analgesic effects, and to possess anxiolytic-like activity [158].…”
Section: Introductionmentioning
confidence: 99%
“…Monotherapy with antiepileptic drugs (AEDs) has been advocated as the preferred regimen for patients with epilepsy (1). However, Mattson et al (2) showed that AED monotherapy resulted in total seizure control in only 39% of the trial population after 1 year.…”
mentioning
confidence: 99%